Effects of body condition score and trace minerals supplements on lactation performance and blood indices of transition dairy ewes - Moradi, Hadi; Ganjkhanlou, Mahdi; Kiatti, Dieu donné; Zali, Abolfazl; Fekri, Ashkan; Palangi, Valiollah; Kalanaky, Somayeh; Nazaran, Mohammad Hassan; Atzori, Alberto Stanislao (Frontiers in Animal Science, 2025)
As an integral part of energy metabolism and immunity, adipose tissue supports lactation’s metabolic demand acting like an energy buffer. In late gestation, ewes with positive energy balance have positive associations with body condition score (BCS), lipid anabolic metabolism might experience oxidative stress. The current study aimed to evaluate the effect of trace minerals (TM) supplementation and different Body Condition Score (BCS) levels on milk production and blood parameters of transition dairy ewes. To achieve the aim, seventy-two dairy ewes (BW = 70.2 ± 0.60 kg, BCS = 3.44 ± 0.2 and parity = 3) were randomly allotted in a 2×3 factorial design of six groups (n = 12/group) according to BCS level (≤3; 3 to 4; ≥4, 2 replications) to be supplemented with organic and inorganic TM (OTM vs. ITM). Milk yield was recorded daily and sampled weekly for fat, protein, lactose, total solids (TS), and milk urinary nitrogen (MUN) analysis. Blood collection occurred on days −30, −20, −10, +24h, +10, +20, and +30 relative to expected lambing whereas the body weight (BW) and BCS change were accessed weekly. Results showed that BCS significantly affected BW and BCS changes during the experimental period (p < 0.01). BCS, TM, and time interaction affect significantly DMI (p < 0.01). Moreover, the same finding was observed for protein (p = 0.03), lactose (p < 0.01), MUN (p < 0.01), and TS (p < 0.01); in both groups with the highest values in BCS ≥ 4. MDA and TOAC were significantly affected by TM supplementation (p = 0.02) and time (p = 0.01), respectively. The cholesterol and ALP concentrations in plasma were affected by BCS and TM; the highest values were observed in BCS ≥ 4 group (OTM = 96.03 mg/dL; ITM = 84.8 mg/dL, p < 0.01) and in BCS from 3 to 4 (OTM = 48.2 U/L; ITM = 46.6 U/L; p = 0.02) for cholesterol and ALP, respectively. TM and BCS interaction influenced cholesterol concentration in the plasma (p = 0.06). TM supplementation significantly influenced plasma ALP; the ITM group had the highest compared to the OTM group (p < 0.05). In conclusion, the results showed that replacing ITM with OTM caused modest improvements in the performance and blood traits of transition ewes. As an integral part of energy metabolism and immunity, adipose tissue supports lactation's metabolic demand acting like an energy buffer. In late gestation, ewes with positive energy balance have positive associations with body condition score (BCS), lipid anabolic metabolism might experience oxidative stress.